Valuable aspects of home rehabilitation in Sweden: Experiences from older adults - Anette Johansson; Marie Ernsth Bravell; Ann Britt Karlsson; Sofi Fristedt (Health Science Reports, 2021)
Abstract Background and aim Home rehabilitation is an increasing service in many countries due to the aging population. The body of knowledge in home rehabilitation is growing but results are inconsistent, and there is still lack of knowledge from user perspectives to guide practice and home rehabilitation programs. The purpose of this study was to explore valuable aspects of home rehabilitation experienced by older adults. Methods Fourteen older persons (nine older adults and five next of kins) were interviewed about their experiences of receiving rehabilitation in their homes. Nine de‐identified interviews were analyzed as secondary data and with qualitative content analysis. Results A familiar home environment, inclusive collaboration, and the mastering of everyday life were aspects of value for older adults in home rehabilitation. Creating a tailor‐made rehabilitation together with competent staff, building trust, and providing a sense of security in their homes were also considered valuable. Conclusion When using the home as an arena for rehabilitation and collaboration, interventions can be planned based on the older adult's unique conditions and the knowledge and skills of the multidisciplinary team, including the older adult and their next of kin. A valuable home rehabilitation can then be achieved that creates motivation, which in the long term probably also generates desired effects for the older adult. More research is needed on older adult's experiences of content in home rehabilitation programs so that practice develops in accordance with citizens' needs, individual resources, and relationships.